'Simplicity' radiofrequency neurotomy of sacroiliac joint: a real life 1-year follow-up UK data. Issue 2 (May 2016) - Anjana Reddy, Vinay S; Sharma, Chhaya; Chang, Kuang-Yi; Mehta, Vivek
Background: Sacroiliac joint (SIJ) pain is considered to be the third most common cause of low back pain with the prevalence of 13–25% in all low back pain patients. Its diagnosis and treatment remain a challenge with the poor evidence base for interventional procedures. Patients with SIJ pain experience a low quality of life, worse than some of the chronic health conditions. Simplicity radiofrequency (RF) neurotomy is a novel technique which tackles some of the problems faced by conventional RF neurotomy and may offer better results in managing pain arising from SIJ. Aim: The purpose of this retrospective review of practice was to look into the effectiveness of Simplicity RF neurotomy in terms of pain relief, quality of health improvement in patients suffering from SIJ pain and complications associated with the procedure. Methodology: Retrospective review of the patients undergoing Simplicity RF neurotomy at a tertiary hospital (April 2012 to June 2013). Pain scores and responses to SF (Short Form) 12 questionnaire before and at 12 months after treatment were compared using the Wilcoxon signed-rank test. Results: Out of 26 patients, 16 were considered for analysis. There was statistically significant reduction in both mean pain score (Numerical Rating Scale, NRS from 8.8 pre-intervention to 4.3 post-intervention) and median pain score (NRS from 9 pre-intervention to 5 post-intervention) with a p-value of <0.001 at 12 months. Reduction in the inter-quartile range of pain score was observed from 8–10 to 2.25–6 (p-value of <0.001). Global health as per SF12 scores showed statistically significant improvement, except in some of the psychological subcategories. The procedure-related pain was the only complication noted. Conclusion: From our data, we can conclude that Simplicity RF neurotomy of lateral branches of S1-S3 along with conventional RF denervation of L5 dorsal ramus may improve pain scores and many components of global health in carefully selected patients.